Novel key gene tenascin C related to extracellular matrix accumulation in diabetic nephropathy kidney tubules: Results of integrative bioinformatics analysis - Liang Zhang; Zheng Wang; Manrong He; Yongdi Zuo; Jun Li; Wanxin Tang (Global Journal of Obesity, Diabetes and Metabolic Syndrome - Peertechz Publications, 2020)
Background: As the incidence of type 2 diabetes increases year by year, the number of individuals diagnosed with Diabetic Nephropathy (DN) has increased steeply. DN is characterized by glomerular sclerosis, tubulointerstitial fibrosis and atrophy. However, most of the previous studies on the pathogenesis of DN were focused on glomeruli, and now more and more evidences show that tubulointerstitial fibrosis plays an important role in the progress of DN. Bioinformatics analysis can be used in discovering disease-causing genes, biomarkers, and therapeutic targets through global analysis. In this study, we used this method to find and verify novel genes in DN. Materials and methods: Microarray expression levels were downloaded from Gene Expression Omnibus datasets. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses were conducted after Differentially Expressed Genes (DEGs) were identified. Hub genes were filtered on the basis of the result of GO enrichment, and functional analysis was performed by browsing the GeneCards website and the latest literatures. The expression levels of all the hub genes in HK2 cells stimulated by high glucose were verified, and TeNascin C (TNC), which is important and interesting, was verified through animal experiment.  Result: The relative expression levels of 54 samples were obtained, and 382 DEGs were identified. 286 GO terms and 100 KEGG pathways were enriched remarkably. Nine of the key genes of interest: MMP7, TNC, LUM, LTF, IGLC1, LYZ, CXCL6, CYP27B1 and FOS were selected and verified in HK2 cells stimulated by high glucose. quantitative Real-Time Polymerase Chain Reaction (qRT-PCR) indicated that the mRNA levels of most of the hub genes were up-regulated and had an accordance rate of approximately 66.7%. In addition, the expression of TNC in renal tubular tissue of STZ-induced diabetic nephropathy rat gradually increased with time.  Conclusion: Several novel key genes were discovered and verified in this study, and TNC plays an important role in the renal fibrosis of DN and is expected to be a new therapeutic target. This study provides a theoretical basis and data resources for further research.